Qualitative and quantitative assessment of immune cells in oral mucosal lichen planus (OMLP) - Sinon, S.H; Rich, A.M; Firth, N.A; Seymour, G.J (Universiti Kebangsaan Malaysia, 2013)
Cell mediated immunity is currently thought to be involved in the pathogenesis of oral mucosal lichen planus (OMLP). However, literature reveals there is no large scale data of immunohistochemistry (IHC) study on these immune cell populations. The aim of this study was to assess and compare immune cell surface identification markers CD3, CD4, CD8, CD19 and CD83 between the OMLP (n=40) and non-specific inflammatory lesions (as control group) (n=10) qualitatively and quantitatively. Kruskal-Wallis and Mann Whitney U tests have been used to make comparison between the test and control group, p values of less than 0.05 was considered to be statistically significant. T cell surface markers (CD3+, CD4+ and CD8+), B cells (CD19+) and mature dendritic cells (CD83+) showed intense immunostaining in OMLP tissues with a significantly higher expression of positive cells than in the control group (p<0.05). CD3, CD4 and CD8+ve T cells were the predominant inflammatory cell type in OMLP rather than CD19+ B cells, supporting the role of Th1 cells in the pathogenesis of OMLP. CD83+ mature dendritic cells were present in the least number and were mostly localized to areas where there were aggregates of lymphocyte. There was a positive correlation and direct relationship between T and B lymphocyte subsets whereby as one subset increased, the other follows.